PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS DANA DEPOSITO DALAM MENINGKATKAN PENGENDALIAN INTERN DI PT BPR KERTA RAHARJA CABANG BANJARAN - Muthmainnah -; Vionita Vadiana vionita; Silvia Catalan Ambag (EKBIS (Ekonomi & Bisnis), 2022)
The purpose of this study is to investigate the extent to which the accounting information System for Cash Receipts on Deposit Funds has an impact on improving internal control at PT BPR Kerta Raharja. The descriptive quantitative research approach was employed, with data collected through field investigations, interviews, and questionnaires. The sample size for this study was 22 employees from PT BPR Kerta Raharja. Based on the study's findings, the hypothesis was accepted after the results of hypothesis testing using the t-test showed a significant level of 0.001 0.000. This indicates a substantial association between the Accounting Information System for Cash Receipts, Deposits, and Internal Control, which validates the premise. Based on the coefficient of determination calculations, the effect of the Accounting Information System for Cash Receipts on Deposit Funds on Internal Control at PT BPR Kerta Raharja Banjaran Branch is 45.7 percent, with the remaining 54.3 percent influenced by other factors not investigated by the author.